POLA KEJADIAN KANKER SERVIKS UTERI PENDUDUK KOTAMADYA SEMARANG - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Tice incidence rate of cervical carcinoma is still relatively high in Indonesia. Therefore, the role of cancer registry is crucial in determining the magnitude of this malignancy problem in order to establish primary prevention programs. All cancer cases in the Semarang Municipality and its surroundings during 1985 to 1989 were collected. Data were gathered from hospitals, clinics, pathology laboratories and community health centres. Age Standardized Rates (ASR) and Age Standardized Cancer Ratios (ASCAR) were used to compute the incidence rate for the Semarang Municipality and ASCAR only for areas outside the Semarang Municipality. The results were compared to the 1970 - 1974 and 1980 - 1981 figures. There has been an increasing number of cervical cancer cases in the Semarang Municipality during the last ten years, but it did not change the age distribution, first in the 45 - 54 age group and second in the 35 - 44 age group.